Identification of PEKKA Characteristics for the Women Empowerment Strategy in Sumedang Regency - Hadi Ferdiansyah (Pusbindiklatren Bappenas, 2022)
Gender income disparity is one of the challenges in realizing community welfare in the SumedangRegency. PEKKA worker is one of the vulnerable objects that need to be improved by the government ofSumedang Regency. This study aims to identify the individual characteristics of PEKKA to determine goalsand priorities for women's empowerment strategies. This study’s method is quantitative research in theform of a description with numbers or numerals (statistics). Reference studies that corroborate theanalysis complement this study's method. The analysis describes the characteristics of female heads ofhousehold in Sumedang Regency. The results showed that PEKKA in Sumedang Regency dominates bymiddle-aged and older women. Their level of education and competence is low, so they commonly workin the informal sector as unassisted entrepreneurs and in the formal sector as laborers. Thesecharacteristics are factors that cause their common welfare. Therefore, the PEKKA EmpowermentProgram in Sumedang Regency needs to involve other regional government affairs, namely Education,Health, Social, Labor, Communication and Information, Cooperatives, Small and Medium Enterprises,Agriculture, and Fisheries. Through this strategy, the PEKKA Empowerment Program can be right on targetto encourage the realization of the welfare of the people of Sumedang Regency.